The effectiveness of caregiver social support is associated with cancer survivors' memories of stem cell transplantation: A linguistic analysis of survivor narratives. Issue 6 (11th June 2015) - Rini, Christine; Emmerling, Dane; Austin, Jane; Wu, Lisa M.; Valdimarsdottir, Heiddis; Redd, William H.; Woodruff, Rebecca; Warbet, Rachel
ABSTRACT: Objective: People who undergo hematopoietic stem cell transplantation are highly dependent on their caregiver during their lengthy treatment and recovery. The effectiveness of their caregiver's social support can profoundly affect their day-to-day treatment experiences and, in turn, how they recall those experiences and are affected by them long after the treatment ends. Method: Our participants were 182 men and women who had undergone a transplant within the previous 9 months to 3 years. They completed baseline measures (including a measure of caregiver social support effectiveness) and then completed three writing assignments describing their transplant experiences. Linguistic analyses were conducted to investigate their use of words indicating negative emotions, cognitive processing (insight and causation), and practical problems with money and insurance. Theory-based hypotheses predicted associations between specific functional types of caregiver support (emotional, informational, and instrumental) and these word categories. Results: As hypothesized, the effectiveness of different functional types of support from a caregiver were uniquely associated with theoretically relevant categories of word use. Structural equation models indicated that more effective caregiver emotional support predicted lower use of negative emotion words; more effective caregiver informational support predicted lower use of causation words; and more effective caregiver instrumental support predicted lower use of words related to money and insurance. Significance of results: Our findings provide insights to guide research on the mechanisms through which caregiver support influences patient outcomes after stem cell transplantation. For instance, research suggests that these kinds of effects could have implications for survivors' current self-concept, psychosocial functioning, and meaning-making.